2009
DOI: 10.1007/s00455-009-9216-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ICD-9 Code 787.2 for Identification of Individuals with Dysphagia from Administrative Databases

Abstract: The aim of this study was to determine the accuracy of dysphagia coding using the International Classification of Diseases version 9 (ICD-9) code 787.2. We used the administrative database of a tertiary hospital and sequential videofluorographic swallowing study (VFSS) reports for patients admitted to the same hospital from January to June 2007. The VFSS reports were abstracted and the hospital's database was queried to abstract the coding associated with the admission during which the VFSS was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 12 publications
1
28
1
Order By: Relevance
“…While we observed disparities in PEG placement by race and socioeconomic status, the incidence of dysphagia did not substantially differ among the different racial groups or quartiles of income in our study population. In administrative databases, dysphagia is largely undercoded and extraction of information on dysphagia based on ICD9-CM coding has low sensitivity 23 ; however, specificity is high, and it is unlikely that dysphagia is differentially undercoded among various racial groups and surrogates or SES. Although the time-to-PEG did not differ among the various groups (median 11 days in minorities vs. 10 days in whites; median 10 days in the low income quartile and all other quartiles combined), it is possible that differential access to repeated speech-language-pathology (SLP) evaluations may account for differences in detection of early recovery.…”
Section: Discussionmentioning
confidence: 99%
“…While we observed disparities in PEG placement by race and socioeconomic status, the incidence of dysphagia did not substantially differ among the different racial groups or quartiles of income in our study population. In administrative databases, dysphagia is largely undercoded and extraction of information on dysphagia based on ICD9-CM coding has low sensitivity 23 ; however, specificity is high, and it is unlikely that dysphagia is differentially undercoded among various racial groups and surrogates or SES. Although the time-to-PEG did not differ among the various groups (median 11 days in minorities vs. 10 days in whites; median 10 days in the low income quartile and all other quartiles combined), it is possible that differential access to repeated speech-language-pathology (SLP) evaluations may account for differences in detection of early recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was likely due to the approach used to identify patients with post-stroke dysphagia: ICD-9 coding. In a study investigating the accuracy of ICD-9 coding of dysphagia for patients who underwent modified barium swallow studies (MBSSs), the code had a positive predictive value (PPV) of 94.4 and a negative predictive value (NPV) of 12.9 [6]. This indicates that when used, the code is accurate but that the code is often not used when a patient does indeed have dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Heckert et al [5] found that 64 % of patients in an inpatient rehabilitation facility had post-stroke dysphagia. It is generally believed that an underreporting of dysphagia via ICD-9 codes exists and that the number of patients with post-stroke swallowing impairment may be even higher than previous reports [6]. Given the frequency of post-stroke dysphagia and the expected growing burden to the US health system, it is helpful to understand the influence of dysphagia on stroke-related healthcare utilization in this time of healthcare reform.…”
Section: Introductionmentioning
confidence: 99%
“…42,46,[49][50][51][52][53][54]57 As a result, a within-group comparison could not be made because there were too few studies within each index test. Methodologic limitations such as these add to the growing list of factors for the underreporting of dysphagia 3,12 and potential attenuation of screening accuracy. 72 There was a moderate amount of heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 There is a > 13-fold increased risk of mortality during hospitalization in rehabilitation patients. 3 These data, combined with the generally accepted belief that dysphagia is underreported, 3,4,12 suggest that patients on medical (ie, not neurologic or oncology) floors may not be recognized as having dysphagia, leading to increased hospitalization lengths and increased health-care costs. 13 Screening for aspiration can, therefore, reduce morbidity, mortality, and costs while increasing health-care quality.…”
mentioning
confidence: 99%